Innovative capitalism needs institutional co-evolution - Ulrich Witt (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The fact that innovative capitalism needs institutional co-evolution has widely been recognized with respect to pro-active institutional adaptations. Examples are the rearrangement and safeguarding of supply chains or the creation of public institutions providing indispensable systemic infrastructure. These adaptations facilitate the innovative expansion of capitalism. Less attention has been paid to the fact that institutional co-evolution is also necessary where the repercussions of major innovative breakthroughs trigger social tensions and environmental damages or ecological hazards. The present paper is therefore devoted to an investigation of the latter kind of institutional co-evolution. These adaptations are usually reactive ones because critical side effects of innovations often only turn out with a delay. The causal nexus between the dynamics of innovative capitalism and the emergence of critical situations that require re-active institutional adaptations will be discussed by means of two examples. One is the crisis of the global commons, most notable the global climate change. The other example is the recent mass migration crisis. Finally, the policy options regarding necessary institutional adaptations will briefly be outlined for the two examples.
Keywords: 650; innovations; capitalism; climate change; institutional crisis; mass migration; mass production